Upper Limb Dysfunction Increases Fear of Falling in People With Stroke (Bangladesh Journal of Medical Science, 2021)
Objective: Our study was planned to investigate the effect of upper limb function on fear of falling in stroke patients.Materials and methods: A total of 61 patients, 33 women with chronic hemiplegia or hemiparesis, were included in the study. Patients’ upper limb motor condition was obtained using the Fugl-Meyer Upper Extremity Rating Scale (FMA), upper limb function Arm Motor Ability Test (AMAT) and fear of falling International Fall Efficacy Scale (FES-I). Standard Mini-Mental Examination scale was used to exclude patients with mental disorders.Results and Discussion: There was a highly significant negative correlation between FES-I and AMAT and FMA scores (p